2012
DOI: 10.1515/ijamh.2012.015
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent suicide in New York City: plenty of room for new research

Abstract: The act of adolescent suicide continues to threaten adolescent populations in New York City (NYC). Consistent positive correlations have been found between a plethora of risk factors present in NYC adolescent populations and suicidal ideations and behaviors. Psychiatric conditions that may contribute to the rate of adolescent suicide in NYC include depression, bipolar disorder, substance abuse and schizophrenia. Unique factors that have been found to contribute to increased rates of completed suicides in NYC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…First, we found that exposure to physical or sexual abuse increased the odds of engaging in suicidal ideation, plans, and attempts during adolescence. These results are in line with previous research, which has shown that exposure to physical or sexual abuse increases the risk of engaging in suicidal behavior (Ganz & Sher, 2012;Miller et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…First, we found that exposure to physical or sexual abuse increased the odds of engaging in suicidal ideation, plans, and attempts during adolescence. These results are in line with previous research, which has shown that exposure to physical or sexual abuse increases the risk of engaging in suicidal behavior (Ganz & Sher, 2012;Miller et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…44,45 Como lo mencionan Beautrais, Dervic y Pompili entre otros, 17,33,36,46,47 el ahorcamiento es el método más utilizado por ser económico, de fácil instalación y no requerir de una planeación laboriosa; aunque es de letalidad más baja que otros métodos. En México, no hay estudios que indiquen las causas por las que este método es el más utilizado tanto en hombres como en mujeres.…”
Section: Discusión Y Conclusiónunclassified
“…Precipitating conditions also consist of moving (Qin, Mortensen, & Pedersen, 2009), homelessness (Ganz & Sher, 2012), problems with the police and legal difficulties (Hoberman & Garfinkel, 1988), and bullying (Luukkonen, Rasanen, Hakko, & Riala, 2009). Adolescents who experience multiple, long-term stressors-particularly those youth with a limited set of problemsolving strategies-are most vulnerable to suicidal behavior (Grover et al, 2009).…”
Section: E Bocciomentioning
confidence: 99%
“…Parental history of psychopathology (Brent et al, 1999), loss of a friend or family member to suicide (Thompson, Kuruwita, & Foster, 2009), paternal and maternal absence (Garfinkel, Froese, & Hood, 1982), maladaptive parenting practices and childhood maltreatment (Johnson et al, 2002), and the experience of physical and/or sexual abuse (Ganz & Sher, 2012) have all been linked to higher rates of suicidal behavior in youth. The quality of family relationships is also an important factor to consider when determining risk for suicide.…”
Section: Section 5: Personal/family Risk Factorsmentioning
confidence: 99%